2012
DOI: 10.3390/w4010123
|View full text |Cite
|
Sign up to set email alerts
|

Improving Water Supply Systems for Domestic Uses in Urban Togo: The Case of a Suburb in Lomé

Abstract: Abstract:The rapid urbanization facing developing countries is increasing pressure on public institutions to provide adequate supplies of clean water to populations. In most developing countries, the general public is not involved in strategies and policies regarding enhancement, conservation, and management of water supply systems. To assist governments and decision makers in providing potable water to meet the increasing demand due to the rapid urbanization, this study sought to characterize existing water s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Several studies have explored the implementation of RWH systems in response to growing water demand in Africa [7,23,24], Asia [25][26][27], USA. [17][18][19][20][21][22][23][24][25][26][27][28] and Australia [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored the implementation of RWH systems in response to growing water demand in Africa [7,23,24], Asia [25][26][27], USA. [17][18][19][20][21][22][23][24][25][26][27][28] and Australia [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The literature reports work in Togo, a sub-Saharan country on the west coast of Africa, where a survey was conducted to characterize the existing water supply systems, which consisted of bucket-drawn water wells, miniature water tower systems, rainwater harvesting, and public piped water. Based on the survey, Ahiablame et al (76) found that the participants preferred a large-scale community water tower to meet their water demands and were also ready to maintain it. The authors recommend this model as the best community water distribution system and further assert the need for research along the same lines to predict models in similar communities of the developing world (76).…”
Section: Comparative Studies On Water Disinfection Techniquesmentioning
confidence: 99%
“…Based on the survey, Ahiablame et al (76) found that the participants preferred a large-scale community water tower to meet their water demands and were also ready to maintain it. The authors recommend this model as the best community water distribution system and further assert the need for research along the same lines to predict models in similar communities of the developing world (76). A huge amount of energy is often required for water treatment and supply globally, and this can be a major hurdle when a water treatment strategy is planned for rural populations, especially in developing countries.…”
Section: Comparative Studies On Water Disinfection Techniquesmentioning
confidence: 99%
“…Problems like a water shortage, water pollution, and environmental deterioration in Togo may get worse and become a major impediment to the country's socio-economic development. Nevertheless, existing studies have only looked at the potential impacts of climate change on ground water with a focus on administrative boundaries [17] and urban water supply [18]. Very few studies have meticulously assessed water security at the hydrological basin level.…”
Section: Background Of the Studymentioning
confidence: 99%